Requirement of protein synthesis for the degradation of host mRNA in Friend erythroleukemia cells infected wtih herpes simplex virus type 1. - Nishioka, Y (1978)
We describe experiments which demonstrate that shortly after infection of Friend erythroleukemia cells with herpes simplex virus (HSV), polyribosomes dissociate and cellular mRNA degrades. Analysis of infected cell extracts on sucrose density gradients demonstrates that the majority of the polyribosomes have dissociated to monoribosomes at 2 h postinfection. Physical measurements of infected-cell RNAs support this conclusion and demonstrate that the polyadenylated RNAs decrease in size. The degradation of mRNA is apparently a stochastic process as judged by the failure to detect a shift in the Crt1/2 when polyadenylated RNA extracted from infected cells at different times is hybridized to globin complementary DNA. In experiments designed to determine whether dissociation of polyribosomes is sufficient to cause degradation of globin mRNA, the amount of globin mRNA in uninfected cells did not change when cells were treated with NaF or pactamycin at concentrations sufficient to dissociate all polyribosomes. In cells infected with UV-irradiated virus polyribosomes dissociate but globin mRNA does not degrade, suggesting that it is possible to separate dissociation from degradation.